Methodology for Cross-Talk Elimination in Simultaneous Voltage and Calcium Optical Mapping Measurements With Semasbestic Wavelengths - Uzelac, Ilija; Crowley, Christopher J.; Iravanian, Shahriar; Kim, Tae Yun; Cho, Hee Cheol; Fenton, Flavio H. (Frontiers in Physiology, 2022)
Most cardiac arrhythmias at the whole heart level result from alteration of cell membrane ionic channels and intracellular calcium concentration ([Ca$^{+2}$]$_{i}$) cycling with emerging spatiotemporal behavior through tissue-level coupling. For example, dynamically induced spatial dispersion of action potential duration, QT prolongation, and alternans are clinical markers for arrhythmia susceptibility in regular and heart-failure patients that originate due to changes of the transmembrane voltage ($V_{\textrm{\scriptsize m}}$) and [Ca$^{+2}$]$_{i}$. We present an optical-mapping methodology that permits simultaneous measurements of the $V_{\textrm{\scriptsize m}}$ - [Ca$^{+2}$]$_{i}$ signals using a single-camera without cross-talk, allowing quantitative characterization of favorable/adverse cell and tissue dynamical effects occurring from remodeling and/or drugs in heart failure. We demonstrate theoretically and experimentally in six different species the existence of a family of excitation wavelengths, we termed semasbestic, that give no change in signal for one dye, and thus can be used to record signals from another dye, guaranteeing zero cross-talk.